2010
DOI: 10.1038/emboj.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear deadenylation/polyadenylation factors regulate 3′ processing in response to DNA damage

Abstract: We previously showed that mRNA 3 0 end cleavage reaction in cell extracts is strongly but transiently inhibited under DNA-damaging conditions. The cleavage stimulation factor-50 (CstF-50) has a role in this response, providing a link between transcription-coupled RNA processing and DNA repair. In this study, we show that CstF-50 interacts with nuclear poly(A)-specific ribonuclease (PARN) using in vitro and in extracts of UV-exposed cells. The CstF-50/ PARN complex formation has a role in the inhibition of 3 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
141
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(160 citation statements)
references
References 64 publications
16
141
0
3
Order By: Relevance
“…Studies have shown that deadenylases localize both in the nucleus and the cytoplasm and are involved in different cellular processes inhibition of mRNA 3' cleavage and activation of deadenylation upon DNA damage. Importantly, the tumor suppressor BARD1 also plays a role in the activation of deadenylation by PARN, 49 suggesting that the activation of deadenylation and the inhibition of 3' mRNA cleavage are part of the same cellular response to DNA damage. Interestingly, the cap binding protein 80 (CBP80) also binds PARN inhibiting its deadenylase activity in untreated cells, 52 representing a possible mechanism by which PARN is recruited to the nascent pre-mRNA and ensuring that PARN does not degrade the poly(A) tail of pre-mRNAs.…”
Section: Nuclear Polyadenylation/ Deadenylationmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that deadenylases localize both in the nucleus and the cytoplasm and are involved in different cellular processes inhibition of mRNA 3' cleavage and activation of deadenylation upon DNA damage. Importantly, the tumor suppressor BARD1 also plays a role in the activation of deadenylation by PARN, 49 suggesting that the activation of deadenylation and the inhibition of 3' mRNA cleavage are part of the same cellular response to DNA damage. Interestingly, the cap binding protein 80 (CBP80) also binds PARN inhibiting its deadenylase activity in untreated cells, 52 representing a possible mechanism by which PARN is recruited to the nascent pre-mRNA and ensuring that PARN does not degrade the poly(A) tail of pre-mRNAs.…”
Section: Nuclear Polyadenylation/ Deadenylationmentioning
confidence: 99%
“…For example, CstF1 can also interact with PARN upon UV treatment. 49 Based on the nature of the factors, it is possible to hypothesize that the PARN/CstF1 interaction might regulate mRNA turnover in different cellular responses. Consistent with this, the CstF1/PARN complex plays a role in deadenylation machineries has been described in the DDR in mammalian cells (Fig.…”
Section: Nuclear Polyadenylation/ Deadenylationmentioning
confidence: 99%
See 3 more Smart Citations